IMPLEMENTASI KEBIJAKAN TENTANG PEDOMAN HIDUP ISLAMI WARGA MUHAMMADIYAH - Abdul Hadi Ahad Amri Yusuf; Erry Sunarya; Ike Rachmawati (Jurnal Governansi, 2021)
The Islamic Life Guidelines of Muhammadiyah Citizens (PHWIM) have not been implemented thoroughly, especially among the education personnel of Muhammadiyah Sukabumi University as one of the elements of Muhammadiyah residents. One of the indications is, there are still education personnel who do not heed the values contained in PHIWM, especially related to managing business charities such as in the last two years there are still delays in entering work and complaints about the performance of education personnel. Thus, the condition is interesting to be used as a research by focusing on the discussion of the implementation of PHIWM policy on education personnel of Muhammadiyah University of Sukabumi. This study aims to analyze the implementation of policies on PHIWM in education personnel of Muhammadiyah University of Sukabumi. The method used in this research is qualitative descriptive method with sampling technique is purposive sampling. The results of this study showed that, the purpose of PHIWM implementation to shape the individual and collective behavior of all Muhammadiyah members who showed good accuracy has not been fully implemented, especially in the educational environment of Muhammadiyah University sukabumi. However, there are several activities that can show a good measure of nudity behavior as an effort in realizing PHIWM objectives such as heeding congregational prayer times, regular study and performance assessment aimed at improving work performance and in accordance with PHIWM values in aspects of life managing business charity for education personnel of Muhammadiyah Sukabumi University (UMMI).